Decision‐making for systemic water risks: insights from a participatory risk assessment process in Vietnam - Wyrwoll, Paul R.; Grafton, R. Quentin; Daniell, Katherine A.; Chu, Hoang Long; Ringler, Claudia; Lien, Le Thi Ha; Khoi, Dang Kim; Do, Thang Nam; Tuan, Nguyen Do Anh (Wiley, 2018)
Systemic threats to food‐energy‐environment‐water systems require national policy responses. Yet complete control of these complex systems is impossible and attempts to mitigate systemic risks can generate unexpected feedback effects. Perverse outcomes from national policy can emerge from the diverse responses of decision‐makers across different levels and scales of resource governance. Participatory risk assessment processes can help planners to understand subnational dynamics and ensure that policies do not undermine the resilience of social‐ecological systems and infrastructure networks. Researchers can play an important role in participatory processes as both technical specialists and brokers of stakeholder knowledge on the feedbacks generated by systemic risks and policy decisions. Here, we evaluate the use of causal modeling and participatory risk assessment to develop national policy on systemic water risks. We present an application of the Risks and Options Assessment for Decision‐Making (ROAD) process to a district of Vietnam where national agricultural water reforms are being piloted. The methods and results of this project provide general insights about how to support resilient decision‐making, including the transfer of knowledge across administrative levels, identification of feedback effects, and the effective implementation of risk assessment processes.